Respuestas

2012-04-04T00:13:20+02:00

      5x           4x            5x(x-1)+4x      5x²-5x+4x       x(5x-1)

a) ------ + -------------= -------------- = --------------- = --------------

     x+1    (x+1)(x-1)       (x+1)(x-1)      (x+1)(x-1)      (x+1)(x-1)

 

   5        1       2x-3     3

b)---- + ------ - ------ - --- =

   4x      x + 1    x^2     4

¡La mejor respuesta!
2012-04-04T00:29:07+02:00

a) 

     5x            4x           5x(x-1)+4x       5x^2-5x+4x      5x^2-x            x(5x-1)

   ------ + -------------=  --------------- =  --------------- = -------------- = ------------

   x+1       (x+1)(x-1)      (x+1)(x-1)        (x+1)(x-1)       (x+1)(x-1)        (x+1)(x-1)

 

 

b)

  El denominador común es 4x^2(x+1)

 

 5x(x+1)+4x^2-(2x-3)(4)(x+1)-3x^2(x+1)        5x^2+5x+4x^2-8x^2-8x+12x+12-3x^3-3x^2

--------------------------------------------------- = --------------------------------------------------

                   4x^2(x+1)                                                    4x^2(x+1)

 

    -3x^3-2x^2+9x+12

=-------------------------

       4x^2(x+1)

 

y ya no se puede simplificar más

 

Saludos

 

TEKNIA